2017
DOI: 10.1021/acs.joc.6b02688
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Controlled Switch in Diastereoselectivities: Enantioselective Construction of Functionalized 3,4-Dihydro-2H-thiopyrano[2,3-b]quinolines with Three Contiguous Stereocenters

Abstract: A tandem Michael-Henry reaction of 2-mercaptoquinoline-3-carbaldehydes with nitroolefins using hydrogen-bonding-based cooperative organocatalysts for the highly diastereodivergent synthesis of chiral functionalized 3,4-dihydro-2H-thiopyrano[2,3-b]quinolines with three contiguous tertiary stereocenters has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Despite their stability to moisture and oxygen and being environmentally friendly, cinchona alkaloids possess various functionalities that are available for chemical modifications . The C9 modification of cinchona alkaloids have been largely reported as ester or ether derivatives and the C9‐amino derivatives such as thiourea or urea derivatives ,,,. In addition, the N1 derivatives of cinchona alkaloids have been applicable in phase transfer catalysis .…”
Section: Methodsmentioning
confidence: 99%
“…Despite their stability to moisture and oxygen and being environmentally friendly, cinchona alkaloids possess various functionalities that are available for chemical modifications . The C9 modification of cinchona alkaloids have been largely reported as ester or ether derivatives and the C9‐amino derivatives such as thiourea or urea derivatives ,,,. In addition, the N1 derivatives of cinchona alkaloids have been applicable in phase transfer catalysis .…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, Xie et al reported a Michael addition–Henry cascade strategy for the synthesis of functionalized 3,4‐dihydro‐2 H ‐thiopyrano[2,3‐ b ]quinolines 22 catalysed by the cinchona based bifunctional thiourea catalyst C‐1 . [ 22b ] The Michael adduct 23 formed after the intermolecular conjugate addition between aromatic thiol 24 and nitrostyrenes 11 undergoes an intramolecular Henry ring closure through less hindered Re‐face of the carbonyl group to furnish the product 22 in excellent yields (90–98 %) with very high stereoselectivities (Scheme 5A).…”
Section: Thiourea‐tertiary Amine Catalyst Based Relay Cascade Catamentioning
confidence: 99%
“…Among the squaramide-based organocatalysts, the alkaloid-squaramide catalyst 135 has provided the best results in the preparation of thiochromans 168 ( Scheme 54 a) [ 183 ]. Following the same idea and type of catalyst, the sulfa-Michael addition to a nitroalkene can be followed by a Henry reaction, allowing the preparation of thiopyran motifs in an enantioselective manner as described in the synthesis of dihydrothiopyrano[2,3- b ]quinolines 169 ( Scheme 54 b) [ 184 ]. For the latter case, the use of another alkaloid-based organocatalysts has allowed to reverse the diastereoselectivity of the transformation.…”
Section: Sulfur Nucleophilesmentioning
confidence: 99%